Visuotactile multimodal fusion with flexible piezo-triboelectric sensors for high-fidelity piano keystroke dynamics decoding - Liang Shen; Man Li; Tingxuan Chen; Qinhua Hu; Bowen Zhang; Enjie Wang; Ji Luo; Mingjun Zhang; Wenjie Wu; Wei Tao (Chemical Engineering Journal, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Ah-level small-molecule proton batteries enabled by a cost-effective gradient-porous composite separator - Yu Li; Rui Li; Xinyu Wang; Mengxiao Li; Junjie Wang; Huige Ma; Mengjing Wu; Haiping Yu; Bei Wang; Huijie Wang; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2026)

The AhR/ROS-mediated lipid peroxidation pathway contributes to 6PPDQ-induced intestine-specific injury in zebrafish during embryonic development - Zhe Wang; Yao Hu; Mingjun Zhu; Xinyue Yang; Qiancheng Huang; Anying Zhang; Xinyan Wang; Hong Zhou (Fish & Shellfish Immunology, 2026)

Condensate gas adsorption and desorption behavior on continental shale matrix under retrograde condensation effect - Mingjun Chen; Maoling Yan; Yili Kang; Hua Liu; Xiaohu Hu; Gang Xiong; Zhehan Lai; Jiajia Bai (Chemical Engineering Journal, 2026)

Humidity: A hidden driver of toxic emissions and asphalt decay in a changing climate - Saba Shariati; Mahour M. Parast; Mingjun Hu; Anais Lostier; Manolis N. Romanias; Albert M. Hung; Elham H. Fini (Science of The Total Environment, 2026)

PRSS23 functions downstream of ZEB1 to promote esophageal squamous cell carcinoma progression by driving M2 polarization of tumor associated macrophages - Wei Chen; Chanjuan Chen; Zhongyun Hu; Fanfan Li; Yao Peng; Mingjun Zhang (Molecular and Cellular Biochemistry, 2026)

Microwave-functionalized sustainable lignin to enhance asphalt oxidation resistance: an oxygen quenching and VOCs adsorption perspective - Hengkang Zhu; Mingjun Hu; Youtian Zhang; Arpatjiang Abudurahman; Yuan Zhu; Jiaxu Cui (Fuel, 2026)

Conversion of wheat straw by black soldier fly larvae and fertilization effects of frass - Xifeng Wang; Ruohan Wang; Junzhao Wei; Rui Hu; Ziling Wang; Haifeng Li; Pengxiao Chen; Jianhang Qu; Mingjun Li (Journal of Asia-Pacific Entomology, 2026)

Air quality benefits of state-led industrial transfer: A staggered difference-in-differences analysis in Chinese cities - Langang Feng; Jin Hu; Minmin Huang; Muhammad Irfan; Mingjun Hu (Urban Climate, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Microwave-assisted functionalization of waste PET plastic with bio-oil: Enhancing compatibility with asphalt through molecular simulation and experimental analysis - Mingjun Hu; Kai Zhu; Qihan Zhang; Guoqiang Sun; Arpatjiang Abudurahman (Fuel, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Miconazole activates MAPK-driven oligodendrogenesis to promote myelin regeneration and neurological recovery after subarachnoid hemorrhage - Gao Mingjun; Xu Ruxiang; Liu Ping; Liu Lingtong; Hu Xiao; Wang Qi; Zou Jiangli; Yin Cheng (Chemico-Biological Interactions, 2025)

Revealing the aging-induced chemical and microstructure evolution of asphalt via AFM-IR and quantum chemistry simulation - Mingjun Hu; Shize Ji; Mingchen Li; Liyuan Liu; Huailei Cheng (Fuel, 2025)

Versatile defect-laden boronizing hard carbon for superior sodium-ion battery efficacy - Jiayi Wen; Cheng Liu; Mingjun Jing; Dan Li; Honghui Hu; Huaxin Liu; Tianjing Wu; Lanhua Yi; Yong Pei; Xue Zhong; Wentao Deng; Guoqiang Zou; et al. (Chemical Engineering Journal, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Study on the self-regeneration strategy of aged asphalt based on magnetic response controlled release microcapsules: A new sustainable self-regenerating pavement system - Yufeng Tian; Lei Xu; Daquan Sun; Hangtian Ni; Zhongbo Chen; Jianxiang Guo; Mingjun Hu (Journal of Cleaner Production, 2025)

Energy consumption and trade liberalization: new micro-evidence from China - Meng Cai; Jin Hu; Mingjun Hu (Environment, Development and Sustainability, 2025)

Water-in-eutectogel electrolytes for scalable solid-state electrochromic devices - Jianbo Deng; Mingjun Chen; Xiang Zhang; Hulin Zhang; Liping Hu; Shuokun Sun; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

Comparative effects of 6PPD and 6PPD-Quinone at environmentally relevant concentrations on hepatotoxicity, glucolipid metabolism and ferroptotic response in adult zebrafish - Zhe Wang; Mingjun Zhu; Yao Hu; Jiaxi Liu; Xiaoyu Ma; Hong Zhou (Environmental Research, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Enhanced nitrogen removal in constructed wetlands filled with iron-carbon substrates: Reexploring unique roles of iron-cycling and electroactive microorganisms - Mingjun Li; Shiyuan Wei; Ruigang Wang; Xin Zhao; Peihao Yan; Jian Zhang; Huaqing Liu; Zhen Hu; Haiming Wu (Journal of Environmental Management, 2025)

Potential function of plant-growth-promoting endophytic Serratia fonticola CPSE11 from Codonopsis pilosula in phytoremediation of Cadmium ion (Cd2+) - Mingjun Yang; Yunxing Fu; Shu Hu; Feifan Leng; Yan Zhuang; Wenbin Sun; Yonggang Wang (Journal of Environmental Management, 2025)

Effects of aging on the nanoscale phase characteristics of bitumen: Insights from chemical composition analysis - Mingchen Li; Mingjun Hu; Shize Ji; Yifu Meng; Lingqing Yuan (Fuel, 2025)

An optimization method for shipping nickel ore with risk and emission considered - Wentao Zhang; Hanlin Hu; Wanwei Fang; Mingjun Ji (Ocean Engineering, 2025)

Strategy research of stakeholders in the construction of agricultural green technology innovation system: an evolutionary game analysis - Jianli Luo; Mingjun Hu; Minmin Huang; Yanhu Bai (Environment, Development and Sustainability, 2025)

Interlayer and O-vacancy engineering co-boosting fast kinetics and stable structure of hydrated sodium ammonium vanadate for aqueous zinc-ion battery - Lang Zhang; Dong Fang; Fei Wang; Jianhong Yi; Mingjun Wang; Te Hu; Yan Zhao (Chemical Engineering Journal, 2025)

Defective carbon-bridged Cu sites to boost oxygen reduction reaction in neutral zinc-air batteries - Tianjing Wu; Honghui Hu; Yufeng Wu; Mingjun Jing; Zhanpeng Chen; Fang Chen; Yansong Bai; Dan Li; Sheng Zhang; Lijie Liu; Wentao Deng; Hongshuai Hou; et al. (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Grifola frondosa polysaccharide's therapeutic potential in oxazolone-induced ulcerative colitis - Xiaoyi Liu; Mingjun Zhang; Shuai Chen; Huijuan Liu; Haoran Ma; Ting Hu; Peng Luo; Shaofeng Wei (Carbohydrate Polymers, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Association of NID2 SNPs with Glioma Risk and Prognosis in the Chinese Population - Jie Hao; Congmei Huang; Weiwei Zhao; Lin Zhao; Xiuxia Hu; WenJie Zhang; Le Guo; Xia Dou; Tianbo Jin; Mingjun Hu (NeuroMolecular Medicine, 2024)

Treatment of landfill leachate by black soldier fly (Hermetia illucens L.) larvae and the changes of intestinal microbial community - Mingjun Ruan; You Li; Chong Ma; Yingying Xie; Wenying Chen; Limei Luo; Xueling Li; Wenfeng Hu; Bin Hu (Journal of Environmental Management, 2024)

Multiscale optimization on polymer-based rejuvenators for the efficient recycling of aged high-viscosity modified asphalt: Molecular dynamics simulation and experimental analysis - Mingjun Hu; Daquan Sun; Bernhard Hofko; Yiren Sun; Johannes Mirwald; Lei Xu (Journal of Cleaner Production, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Phase transformations and microstructure evolution of boron-containing iron concentrate during roasting under CO-CO2-N2 atmosphere: Synergistic effect of soda-ash and CO concentration - Jinxiang You; Meishi Hu; Mingjun Rao; Xin Zhang; Jun Luo; Zhiwei Peng; Guanghui Li (Minerals Engineering, 2024)

A novel WCO-MDI reactive rejuvenation method for aged SBS modified asphalt toward sustainable asphalt pavements - Yurou Zhang; Changjun Zhou; Ping Zou; Mingjun Hu; Peng Cao (Journal of Cleaner Production, 2024)

Vertical decentralization, environmental regulation, and enterprise pollution: An evolutionary game analysis - Yuntao Wu; Jin Hu; Muhammad Irfan; Mingjun Hu (Journal of Environmental Management, 2024)

Rainstorm waterlogging vulnerability assessment of subway stations in the central area of Tianjin - Zishuang Xiao; Qiang Gao; Xingshuai Hou; Mingjun Ma; Beibei Hu; Wenfang Song; Lifei Jia (Hydrological Sciences Journal, 2023)

Enhancing high-quality development in regional innovation ecosystems - Biao Hu; Pengsong Guo; Mingjun Gao (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Does green finance promote low-carbon economic transition? - Mingjun Hu; Zhengling Sima; Shiyu Chen; Minmin Huang (Journal of Cleaner Production, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

SARS-COV-2 spike protein promotes RPE cell senescence via the ROS/P53/P21 pathway - Yuhang Zhang; Xuyan Peng; Mengjiao Xue; Jingjing Liu; Guohui Shang; Mingjun Jiang; Dandan Chen; Baixue Liu; Yuxuan Wang; Xiaolin Jia; Jianqing Xu; Fengyan Zhang; et al. (Biogerontology, 2023)
SARS-Cov-2 infection, which has caused the COVID-19 global pandemic, triggers cellular senescence. In this study, we investigate the role of the SARS-COV-2 spike protein (S-protein) in regulating the senescence of RPE cells. The results showed that administration or overexpression of S-protein in ARPE-19 decreased cell proliferation with cell cycle arrest at the G1 phase. S-protein increased SA-β-Gal positive ARPE-19 cells with high expression of P53 and P21, senescence-associated inflammatory factors (e.g., IL-1β, IL-6, IL-8, ICAM, and VEGF), and ROS. Elimination of ROS by N-acetyl cysteine (NAC) or knocking down p21 by siRNA diminished S-protein-induced ARPE cell senescence. Both administrated and overexpressed S-protein colocalize with the ER and upregulate ER-stress-associated BIP, CHOP, ATF3, and ATF6 expression. S-protein induced P65 protein nuclear translocation. Inhibition of NF-κB by bay-11-7082 reduced S-protein-mediated expression of senescence-associated factors. Moreover, the intravitreal injection of S-protein upregulates senescence-associated inflammatory factors in the zebrafish retina. In conclusions, the S-protein of SARS-Cov-2 induces cellular senescence of ARPE-19 cells in vitro and the expression of senescence-associated cytokines in zebrafish retina in vivo likely by activating ER stress, ROS, and NF-κb. These results may uncover a potential association between SARS-cov-2 infection and development of AMD.

Spatial variations, health risk assessment, and source apportionment of soil heavy metals in the middle Yellow River Basin of northern China - Futian Liu; Xueqiu Wang; Shuang Dai; Jian Zhou; Dongsheng Liu; Qinghai Hu; Wei Wang; Mingjun Xie; Yuexin Lu; Mi Tian; Hao Yan (Journal of Geochemical Exploration, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Analysis of public emotion on flood disasters in southern China in 2020 based on social media data - Mingjun Ma; Qiang Gao; Zishuang Xiao; Xingshuai Hou; Beibei Hu; Lifei Jia; Wenfang Song (Natural Hazards, 2023)

Bridging resource disparities for sustainable development: A comparative analysis of resource-rich and resource-scarce countries - Yanchao Feng; Jin Hu; Sahar Afshan; Muhammad Irfan; Mingjun Hu; Shujaat Abbas (Resources Policy, 2023)

How can blockchain technology promote food safety in agricultural market?—an evolutionary game analysis - Yanhu Bai; Zhuodong Yang; Minmin Huang; Mingjun Hu; Shiyu Chen; Jianli Luo (Environmental Science and Pollution Research, 2023)

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

How does agricultural production agglomeration affect green total factor productivity?: empirical evidence from China - Jianli Luo; Minmin Huang; Mingjun Hu; Yanhu Bai (Environmental Science and Pollution Research, 2023)

A post-synthetic modified NH2-MIL-125 (Ti) catalyst for boosting photochemical Cr (VI) reduction - Xin Zhang; Yuting Huang; Mingjun Bao; Yue Gao; Xiaoxue Zhou; Lexin Liu; Ye Hu; Zhiguang Zhang (Process Safety and Environmental Protection, 2023)

Atmospheric acid leaching of powdery Ni-Co-Fe alloy derived from reductive roasting of limonitic laterite ore and recovery of battery grade iron phosphate - Mingjun Rao; Jing Chen; Tao Zhang; Meishi Hu; Jinxiang You; Jun Luo (Hydrometallurgy, 2023)

How does innovation consortium promote low-carbon agricultural technology innovation: An evolutionary game analysis - Jianli Luo; Mingjun Hu; Minmin Huang; Yanhu Bai (Journal of Cleaner Production, 2023)

Thermoreversible aging in biorejuvenated asphalt binder - Jianmin Ma; Mingjun Hu; Tong Lu; Daquan Sun; Simon A.M. Hesp (Journal of Cleaner Production, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

Anti-oxidation polyimide-based hybrid foams assembled with bilayer coatings for efficient electromagnetic interference shielding - Longhai Zhuo; Yaling Cai; Dong Shen; Pengfei Gou; Mingjun Wang; Guang Hu; Fan Xie (Chemical Engineering Journal, 2023)

Preparation and properties of zeolite-fly ash-slag composite porous materials: CO2 adsorption performance and mechanical property - Wei Lu; Juan Li; Guansheng Qi; Xiangming Hu; Qian Zhang; Mingjun Wang; Maoyuan Zhang (Environmental Science and Pollution Research, 2022)

Optimized structural parameters and heat extraction capacity of a mixing device for constant pressure CO2 mineralization using alkaline waste - Wei Lu; Yang Yuan; Xiangming Hu; Guansheng Qi; Lulu Sun; Maoyuan Zhang; MingJun Wang; Min He (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Outdoor air pollution enhanced the association between indoor air pollution exposure and hypertension in rural areas of eastern China - Guoao Li; Huanhuan Lu; Wenlei Hu; Jianjun Liu; Mingjun Hu; Jialiu He; Fen Huang (Environmental Science and Pollution Research, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Occurrence, seasonal variation and environmental impact of phosphorus flame retardants in a large scale wastewater treatment plant - Zhineng Liu; Mingjun Deng; Qihang Wu; Dave T. F. Kuo; Lixi Zeng; Zhu Wang; Ying Zhang; Xinyu Liu; Shengyu Liu; Junyan Liang; Xiaodong Hu; Bixian Mai (Environmental Science and Pollution Research, 2019)

Stability analysis of the Xinlu Village landslide (Chongqing, China) and the influence of rainfall - Luqi Wang; Yueping Yin; Zhihua Zhang; Bolin Huang; Yunjie Wei; Peng Zhao; Mingjun Hu (Landslides, 2019)

Recent Progress in Dual-Polarization Radar Research and Applications in China - Kun Zhao; Hao Huang; Mingjun Wang; Wen-Chau Lee; Gang Chen; Long Wen; Jing Wen; Guifu Zhang; Ming Xue; Zhengwei Yang; Liping Liu; Chong Wu; et al. (Advances in Atmospheric Sciences, 2019)

Nutrition and water temperature regulate the expression of heat-shock proteins in golden pompano larvae (Trachinotus ovata, Limmaeus 1758) - Laetitia Allais; Chao Zhao; Mingjun Fu; Jing Hu; Jian G. Qin; Lihua Qiu; Zhenhua Ma (Fish Physiology and Biochemistry, 2019)

Assessing pollution and risk of polycyclic aromatic hydrocarbons in sewage sludge from wastewater treatment plants in China’s top coal-producing region - Qihang Wu; Zhineng Liu; Junyan Liang; Dave T. F. Kuo; Shejun Chen; Xiaodong Hu; Mingjun Deng; Haozhi Zhang; YueHan Lu (Environmental Monitoring and Assessment, 2019)

Role of αKlotho and FGF23 in regulation of type II Na-dependent phosphate co-transporters - Ming Chang Hu; Mingjun Shi; Orson W. Moe (Pflügers Archiv - European Journal of Physiology, 2019)

Human biomonitoring of eight trace elements in urine of residents living in rural areas along the Yangtze River, China - Yanjie Cui; Qi Zhong; Mingjun Hu; Jie Sheng; Yuanyuan Yang; Ling Liang; Xiaodong Wang; Yuwei Yang; Mengmeng Zhou; Fen Huang (Environmental Science and Pollution Research, 2017)

Trends and uncertainties in surface air temperature over the Tibetan Plateau, 1951–2013 - Wei Hua; Guangzhou Fan; Yiwei Zhang; Lihua Zhu; Xiaohang Wen; Yongli Zhang; Xin Lai; Binyun Wang; Mingjun Zhang; Yao Hu; Qiuyue Wu (Journal of Meteorological Research, 2017)

Assessment of effectiveness of nature reserves on the Tibetan Plateau based on net primary production and the large sample comparison method - Yili Zhang; Zhongjun Hu; Wei Qi; Xue Wu; Wanqi Bai; Lanhui Li; Mingjun Ding; Linshan Liu; Zhaofeng Wang; Du Zheng (Journal of Geographical Sciences, 2016)

Characterization of the Zhikong Scallop (Chlamys farreri) Mantle Transcriptome and Identification of Biomineralization-Related Genes - Mingjun Shi; Ya Lin; Guangrui Xu; Liping Xie; Xiaoli Hu; Zhenmin Bao; Rongqing Zhang (Marine Biotechnology, 2013)

Production of recombinant human lysozyme in the milk of transgenic pigs - Jia Tong; HengXi Wei; XiaoFang Liu; WenPing Hu; MingJun Bi; YuanYuan Wang; QiuYan Li; Ning Li (Transgenic Research, 2011)

Functional characterization of the promoter region of human TNFAIP1 gene - Mingjun Liu; Zhenhua Sun; Aidong Zhou; Hong Li; Liping Yang; Chang Zhou; Rushi Liu; Xiang Hu; Jianlin Zhou; Shuanglin Xiang; Jian Zhang (Molecular Biology Reports, 2010)